Demographic Factors Associated with Hantavirus Infection in Bank Voles (Clethrionomys glareolus) - Olsson, Gert E.; White, Neil; Ahlm, Clas; Elgh, Fredrik; Verlemyr, Ann-Christin; Juto, Per; Palo, R. Thomas
The bank vole (Clethrionomys glareolus) is the natural reservoir of Puumala virus (PUUV), a species in the genus Hantavirus. PUUV is the etiologic agent of nephropathia epidemica, a mild form of hemorrhagic fever with renal syndrome. Factors that influence hantavirus transmission within host populations are not well understood. We evaluated a number of factors influencing on the association of increased PUUV infection in bank voles captured in a region in northern Sweden endemic for the virus. Logistic regression showed four factors that together correctly predicted 80% of the model outcome: age, body mass index, population phase during sampling (increase, peak, or decline/low), and gender. This analysis highlights the importance of population demography in the successful circulation of hantavirus. The chance of infection was greatest during the peak of the population cycle, implying that the likelihood of exposure to hantavirus increases with increasing population density.